Brand Naming Behavior Defining SMMEs in eThekwini - Kunene, Lindiwe N.; Phiri, Maxwell (Journal of Economics and Behavioral Studies, 2018)
Branding is an integral part to the success of any and every business. Appropriate brand strategies contribute to brand equity of the organization leading to increased turnover and profits of positive turnover for organizations. Application of properly planned brand naming processes could save SMMEs and reduce the high failure rate experienced by this sector, in South Africa currently. Branding helps businesses to define who they are and guides their overall strategy. Branding strategies begin with the brand naming process. There are scientifically proven models that govern this process which have been used by successful businesses, globally. This study sought to find the current brand naming processes as implemented by SMMEs in the eThekwini Municipality area in Durban, South Africa. This was the first step in developing a model for brand naming for SMMEs in eThekwini. The study therefore used descriptive-exploratory ethos to conduct the research, guided by the epistemological, ontological and axiological assumptions. Demographic dimensions, ownership of the brand naming process, traits in the naming process and brand naming strategies considered were used to reach conclusions that define these entities in eThekwini. Research outcomes found that a lack of resources and knowledge were the main impediments distorting appropriate brand naming processes.